PENDAMPINGAN PENINGKATAN KAPASITAS PRODUKSI DAN PEMASARAN MINUMAN HERBAL DI POSBINDU DAHLIA RW 01 PETUKANGAN SELATAN - M. Aji Bimantara; Didik Haryadi Raharjo (CV. Denasya Smart Publisher, 2025)
Indonesia holds great potential in the development of herbal-based products, one of which is the traditional beverage kunyit asem (turmeric tamarind), known for its various health benefits. However, small-scale producers still face challenges in marketing and distributing their products effectively. This community service program was conducted at Posbindu Dahlia RW 01, Petukangan Selatan, aiming to enhance the partners' capabilities in promoting kunyit asem herbal drinks through digital marketing strategies. The method used was participatory and collaborative, encompassing problem identification, field surveys, material preparation, digital marketing training, and ongoing monitoring and evaluation. The results showed significant improvement in participants’ skills and knowledge in utilizing social media platforms such as WhatsApp Business and Instagram, improving product packaging, and strengthening brand identity. Post-training evaluations revealed that over 80% of participants felt more confident in marketing their products digitally. This activity demonstrates that a digital marketing approach can be an effective solution in developing traditional herbal beverage businesses to be more competitive in modern markets.